Adolescents’ experiences of acceptance and commitment therapy for depression: An interpretative phenomenological analysis of good-outcome cases - Ma, Jinping; Ji, Lili; Lu, Guohua (Frontiers in Psychology, 2023)
Acceptance and commitment therapy (ACT) has been shown to help treat depression. However, little is known about the patient's experiences with ACT. This study aimed to learn how it was used in adolescents with major depressive disorder who have achieved good treatment outcomes. Five adolescents with major depressive disorder with good treatment outcomes of ACT were enrolled in the semi-structured qualitative interview and analyzed using systematic textual condensation and interpretative phenomenological analysis. Four primary themes emerged from the investigation. "Therapist relationships and characteristics" describes the therapist's receptiveness and respect for adolescents with depression and having a trustworthy and sincere therapist. "Spaces to explore and experience" describes the ongoing process and content of acceptance of negative emotions and mindfulness practices in the healing process. "Do important things" refers to values and committed action. The "time settings" include the frequency and duration of treatment. Adolescents make positive changes with a receptive and respectful therapist by exploring themselves in a genuine and trusting therapeutic relationship. Improvement seems to come from being open to all thoughts and feelings and developing the ability to live in the present moment. Teenagers attach great importance to value-oriented behaviour. Therefore, treatment should target the critical areas of depressed adolescents to guide them towards recovery effectively.